Concentration Effect of Watermelon Skin Extracts (Albedo) as Organic Inhibitors on the Corrosion of Iron Nails in 3% NaCl Medium Solution - Nurhikmah Nurhikmah; Minarni R. Jura (Universitas Tadulako, 2021)
This study aimed to determine the concentration effect of skin extract in watermelon on the inhibition of corrosion rates of iron nails in the corrosive medium of NaCl solution and seawater as a comparison. The study began with the first maceration of the skin in watermelon and then followed by evaporation to produce extracts specific gravity 0,097 gram/mL as inhibitors with variations in concentrations of 1, 2, 4, 8, and 16%. The method of determining the corrosion rate used was the weight loss method from the 7-day immersion process. The results showed that the greatest corrosion inhibition efficiency occurred at a concentration of 8% for immersion with 3% NaCl corrosive medium and 4% concentration for immersion in seawater with the efficiency of 11.56% and 22.15%, respectively. Based on the results of the study, it was found that each addition of extract in watermelon can affect the effectiveness of inhibition.